Attitudes of Female Students in the Special Education Department Towards their Academic Major: A Comparative Study Between Alasmarya Islamic University and Misurata University - Al-Zoubi, Salma Abdulaziz; Al-Barni, Youssef Mohamed; Abu Zandah, Aya Al-Shaab (The annual Scientific Conference for Under and Postgraduate Students at the University., 2004)
The aim of this research is to identify the attitudes of female students in the Special Education Department at the Faculty of Humanities in Zliten and the Faculty of Education in Misurata towards their academic major. It also aims to reveal the statistically significant differences in the attitudes of female students in the Special Education Department towards their academic major according to the college variable (Faculty of Humanities in Zliten and Faculty of Education in Misurata). Additionally, it seeks to uncover the statistically significant differences in the attitudes of female students in the Special Education Department towards their academic major according to the semester variable, as well as the statistically significant differences in the attitudes of female students in the Special Education Department towards their academic major according to the age variable. The researchers used the descriptive analytical method and reached the following results: Female students in the Special Education Department at both the Faculty of Humanities (Alasmarya Islamic University) in Zliten and the Faculty of Education (Misurata University) have a high positive attitude towards the Special Education major. There are statistically significant differences between the students in their attitudes towards the Special Education major according to the college variable, meaning that the attitude of students at the Faculty of Education (Misurata University) is higher than that of students at the Faculty of Humanities (Alasmarya Islamic University). There are no differences between the students in their attitudes towards the Special Education major according to the seniority in semesters variable, and there is no statistically significant relationship between the age of the students and their attitudes towards the Special Education major.
Keywords: Attitudes of Female Students; Special Education; Academic Major